Media, mobilization and the Umbrella Movement - Lee, Francis L.F. 1975- (Routlege, 2017)
The Umbrella Movement in Hong Kong caught the world's attention and imagination at the end of 2014. The 79-day occupation campaign took on some of the characteristics of the recent wave of large-scale protest movements around the world, including the prominent roles played by the media - both conventional and digital - in the mobilization and communication processes of the movement. 0This edited volume, 'Media, Mobilization and the Umbrella Movement', brings together nine contributions which examine various aspects of the media-movement nexus, including the power of televised images to mobilize people, the role of social media in the insurgent public sphere, young activists' social media strategies, media influence on citizens' understanding of civil disobedience, the government's response to digital media tactics, public discourses about the rule of law, and local and foreign media coverage of the movement. We believe that this high-quality collection can not only enhance our understanding of the Umbrella Movement, but also facilitate and trigger more research and dialogue comparing the Umbrella Movement with other similar protest movements around the world. This book was originally published as a special issue of the 'Chinese Journal of Communication'